NMR structure of a ribosomal RNA hairpin containing a conserved CUCAA pentaloop - Nagaswamy, Uma (Oxford University Press, 2001)
The structure of a 23 nt RNA sequence, rGGACCCGGGCUCAACCUGGGUCC, was elucidated using homonuclear NMR, distance geometry and restrained molecular dynamics. This RNA is analogous to residues 612–628 of the Escherichia coli 16S rRNA. The structure of the RNA reveals the presence of a pentaloop closed by a duplex stem in typical A-form conformation. The loop does not form a U-turn motif, as previously predicted. A non-planar A·C·A triple base interaction (hydrogen bonds A13 NH6–C10 O2 and C10 N3–A14 NH6) stabilizing the loop structure is inferred from structure calculations. The CUCAA loop structure is asymmetrical, characterized by a reversal of the phosphodiester backbone at the UC step (hydrogen bond C12 NH4–C10 O2′) and 3′-stacking within the CAA segment. Loop base U11 is oriented towards the major groove and the consecutive adenosines on the 3′-end of the loop are well stacked, exposing their reactive functional groups in the minor groove defined by the duplex stem. The solution structure of the loop resembles that seen in the 3.3 Å X-ray structure of the entire 30S subunit, where the analogous loop interacts with a ribosomal protein and a receptor RNA helix.